PENDIDIKAN KELUARGA BAGI MASA DEPAN ANAK YANG GEMILANG (MENURUT AMSAL 1:8-9) - Suriyanti, Intan; Sitompul, Peronika (UPPM Sekolah Tinggi Teologi Tabgha Batam, 2025)
Every parent wants the best for their child. For this reason, parents usually provide education in the form of teaching, advice, guidance and examples for their children so that they grow and develop well in order to obtain a good future. As Christians, parents will provide the best upbringing for their children in accordance with the teachings of the Bible which is a life guide that is useful for teaching, declaring mistakes and for correcting behavior and for educating people in truth (2 Tim 3:16). Children should follow the teachings and advice of their parents for their own good. As written in Proverbs 1:8-9, which reminds children to follow the teachings and advice of their parents, so that they get decorations in the form of beautiful bouquets for their heads and necklaces for their necks. Therefore, it is interesting to know how important education is for children as written in Proverbs 1:8-9 for the child's future. This research was carried out in the form of an exegesis by analyzing the contents of the Bible focusing on three topics related to the contents of the book, namely the author book, date and place of writing of the book and the reader of the book. Investigating these three topics helps the interpreter understand the contents of the related book or, conversely, the contents of the book help the interpreter find answers to these three topics, then by becoming more familiar with these three topics the interpreter is more likely to understand the purpose of the book being written. Apart from that, literature searches were also carried out from various books and other sources to strengthen the research. Based on the results of the research, assisted by literature searches, it was concluded that children who follow their father's teachings and follow their mother's teachings will have a brilliant future, because glory will follow them. This is because every child who adheres to the upbringing and teachings of his parents will always try to do their best. This will certainly have an impact on the success of their lives, and even obtain glory from God.